Epidemiology of drug-resistant tuberculosis among hospitalized children with tuberculosis in southwest China, 2017–2024 - Dong-Mei Wang; Qi An; Qing Yang; Yi Liao (Frontiers in Microbiology)
BackgroundTo describe the demographic and clinical characteristics of pediatric tuberculosis (TB) inpatients diagnosed with resistance to any anti-tuberculosis drug [drug-resistant tuberculosis (DR-TB)] in southwest China.MethodsPatients aged ≤14 years with clinically diagnosed pediatric TB were recruited from January 2017 to December 2024 at specialty hospitals in southwest China based on either etiology or clinical confirmation. Hospitalization records were extracted for each patient.ResultsAmong 2,208 pediatric TB patients, 90 (4.08%) had DR-TB. DR-TB cases had an average age of 10.94 ± 3.52 years, with a male-to-female ratio of 0.76:1. The highest proportion was in the 10–14-year age group (72.2%), and prevalence was significantly higher in girls than boys. By disease type, 13.33% had pulmonary tuberculosis, 5.56% had extrapulmonary tuberculosis (EPTB), and 81.11% had combined TB. The most common form of EPTB was lymph node TB (30.00%), followed by pleural TB (20.71%), abdominal TB (19.29%), and TB meningitis (14.29%). Among the 90 pediatric DR-TB cases, 74.4% were primary patients (with rifampicin-resistant TB and multidrug-resistant TB accounting for 36.7 and 30.0%, respectively). The Tibetan ethnic group had the highest proportion of DR-TB cases (63.3%). Over the 8-year period, most pediatric DR-TB cases were from western Sichuan (including Ganzi, Aba, and Liangshan minority areas), with the highest number in the Ganzi Tibetan Autonomous Prefecture.ConclusionPediatric DR-TB in southwest China predominantly affects older girls, with primary cases representing a high proportion. The western regions of Sichuan bear a relatively high burden. Public health efforts should prioritize awareness, screening, and early diagnosis of pediatric DR-TB in high-risk areas to prevent transmission.